‘Una Monaca, opera di Leonardo da Vinci’ - Forcellino, Maria (Incontri. Rivista europea di studi italiani, 2023)
‘A Nun, a Work of Leonardo da Vinci’ This essay, starting from a fragment of information concerning a copy of the Gioconda (Mona Lisa) from the unpublished 1771 Roman inventory of the collection of paintings by Maria Laura Dal Pozzo Boccapaduli, reconstructs the critical fortune in the eighteenth century of an important sixteenth-century painting nowadays exhibited in the Uffizi (Ridolfo del Ghirlandaio, Portrait of a Woman (The Nun), oil on panel, 65x48 cm, Inv. 1890, no. 7380). The work is a portrait of a woman whose author is discussed but was in the eighteenth and nineteenth century believed to be a Leonardo autograph. The portrait was well known to fellow artists and connoisseurs in eighteenth-century Florence. This research makes clear that the work is also documented in the art literature field as belonging to the Niccolini collection. For the austere shape of her clothes, the woman on the panel was considered to be ‘a nun’ for a long time and therefore known as ‘Leonardo’s Nun’. Its fame also reached Rome when a Tuscan artist, Giovanni Sorbi, who had been called to draw up the inventory of the Dal Pozzo Boccapaduli paintings, identified the copy of the Gioconda from the collection (Leonardo da Vinci’s workshop, La Gioconda, oil on panel transferred to canvas, 70x50,5 cm, Rome, National Galleries of Ancient Art, Palazzo Barberini, Inv. 864) as ‘Leonardo’s Nun’, attributing to her a very high price (500 scudi). The confusion between the Nun and the Mona Lisa in the eighteenth century testifies the little knowledge that the public had until that date of the iconography of the Gioconda, even among connoisseurs, in Florence and abroad.